Validating the Hypoglycaemic and Hypotensive Roles of Salvia serotina (Chicken Weed) in Normal Healthy Sprague–Dawley Rats - Tameika Bartley; Paul Reese; Sophie Turfus; Ruby Alexander-Lindo (The Scientific World Journal)
Diabetes mellitus (DM) is an endocrine disease and is characterized by hyperglycaemia. Salvia serotina L. (chicken weed) has been used in traditional medicine to treat various ailments including DM. Aqueous, hexane, ethyl acetate, and methanol crude extracts of S. serotina L. were investigated for their anti-oxidant activities and hypoglycaemic and hypotensive effects in normal, healthy Sprague–Dawley rats using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, oral glucose tolerance test (OGTT), and the CODA noninvasive blood pressure system to determine systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), and heart rate (HR). The aqueous extract caused a free radical scavenging effect with an IC50 value of 10.2 ± 1.01 µg/mL versus vitamin C (9.42 ± 1.01 µg/mL). The extract lowered the blood glucose concentration at the 150 minute interval (5.00 ± 0.22 mM vs. 6.51 ± 0.33 mM; p=0.004) and the 180 minute interval (4.77 ± 0.27 mM vs. 5.93 ± 0.0.30 mM; p=0.015). The hexane extract gave significant hypoglycaemic activity at the 120 minute interval (4.54 ± 0.21 mmol/L vs. 5.50 ± 0.17 mmol/L; p=0.005). The hexane extract also significantly lowered the SBP (132 ± 6 mm Hg; p=0.014), DBP (106 ± 7 mm Hg; p=0.034), and MAP (114 ± 7 mm Hg; p=0.023) versus the controls SBP (156 ± 4 mm Hg), DBP (132 ± 8 mm Hg), and MAP (140 ± 6 mm Hg). Bioassay-directed purification of the hexane extract yielded 3,7,11-trimethyl-1,6,10-dodecatrien-3-ol (1), 3,7,11-trimethyl-2,6,10-dodecatrien-1-ol (2), and 5,22-stigmastadien-3β-ol (3) as active principles. Hence, S. serotina L. showed anti-oxidant, hypoglycaemic, and hypotensive effects in the rats and may have potential applications in the treatment of diabetes.